2020
DOI: 10.1088/1755-1315/548/3/032013
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the environmentally safe technology for the processing of liquid animal breeding

Abstract: The article discusses the optimization of parameters of environmentally friendly technologies in the processing of liquid waste in order to obtain organic fertilizer and liquid phase for irrigation and increase the fertility of agricultural land. These parameters are established on the basis of studies of the processes of reagent fractionation of highly concentrated biogenic elements of liquid waste from pig farms. The regression equations were used for the experimental data obtained by studying the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Fertilizers require drying for further processing and bringing to trade appearance. The dehydration process is widely used as a method of removing moisture using various equipment and installations [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Fertilizers require drying for further processing and bringing to trade appearance. The dehydration process is widely used as a method of removing moisture using various equipment and installations [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Several publications [11][12][13][14] substantiated the rationality of the method of reagent treatment of pig waste to obtain organic mineral fertilizers. The effectiveness of their practical application in increasing the yield of agricultural crops is considered.…”
Section: Introductionmentioning
confidence: 99%
“…The results of studies [11] indicated that the use of manure is a viable strategy for regulating crop yields due to increased soil fertility. The authors of the article have developed methods for obtaining organic mineral fertilizers based on liquid waste from pig farms [12][13][14]. In 2019, the effectiveness of organic mineral fertilizer was evaluated at the D. N. Pryanishnikov Scientific Research Institute of Agrochemistry, when growing spring wheat of the "Zlata" variety in vessels under phytotron conditions.…”
mentioning
confidence: 99%